SOAR as an Effective Community-based Response in Anti-Trafficking Movements - Dhungel, Rita (Journal of Advanced Academic Research, 2022)
Grounded in the narratives of women from rural communities who were forced to migrate to Kathmandu, the capital of Nepal, and later India, this paper critically examines the meaningful involvement of trafficking survivors for sexual exploitation in anti-trafficking movement in Nepal. Using the SOAR (Stop, Observe, Ask, and Respond) model, this paper explores the community-based responses to address the issues of human trafficking and post-trafficking. This paper is guided by migratory and intersectionality frameworks. Using the frameworks, Participatory Action Research (PAR), a transformative and an empowerment methodology, was conducted with eight female trafficking survivors who were exploited for sexual exploitation. PAR was used to critically understand intersectional gender oppression escalated the vulnerability of women to trafficking and made the women “doubly victimized” in their post trafficking. Through engaging in the study process, PAR allowed survivors to critically understand their own oppression and develop strategies to effectively act towards ending forced migration and trafficking. Using a thematic analysis, the collected information was categorized, and coded. The research team included the researcher and the trafficking survivors, who are recognized as “co-researchers” in this paper, identified and used a wide range of pragmatic approaches and tools such as street dramas, interactive sessions, peer interviews and meetings with political leaders. These approaches provided the survivors with an opportunity not only to share their voices and experiences on migration and trafficking, but also to highlight transformative impacts, including personal and social transformation.